An Infrequent Extraintestinal Manifestation of Ulcerative Colitis: Pulmonary Necrobiotic Nodules - Myer, Adam S (Cureus, 2020)
Pulmonary necrobiotic nodules are a rare extraintestinal manifestation (EIM) of inflammatory bowel disease (IBD), which are often overlooked when diagnosing cavitary pulmonary nodules. We present this case to highlight the importance of a thorough differential diagnosis, which includes EIMs of ulcerative colitis (UC), in this case as necrobiotic nodules. Herein, we present a 25-year-old male patient with a history of poorly controlled UC who presented with fevers, left-sided abdominal pain, and bloody diarrhea. Imaging revealed cavitary pulmonary nodules without an infectious or malignant etiology. Lung biopsy and pathology confirmed a diagnosis consistent with necrobiotic nodules.